SISTEM PAKAR MENDETEKSI KERUSAKAN CRANE NK-200H-V DENGAN CERTAINTY FACTOR BERBASIS WEB - Andreas, Yose; Yenni, Yusli (Computer Science and Industrial Engineering, 2020)
Many contractors now definitely use Crane because the use of Crane can carry out work more quickly and efficiently. Crane is always needed in large quantities because in a day there is a lot of constructions going on. Crane Kato NK-200H-V is a tool that is used to simplify development work and can also be used in other fields. Crane Kato NK-200H-V is a very important tool in the construction process, without the tool the construction process will be slower, but in the process of using the Crane, damage can occur. When the damage occurs, the technician will be called to check what parts are damaged and a very careful check is needed, therefore the construction progress will be hampered and result in losses. So the damage needs to be system deployed because not all Crane users know the problems that occur in the Crane and also the solution. In the expert system there is a Certainty Factor method that is used to ascertain an uncertain problem and calculate the percentage value based on the symptoms given. Crane Kato NK-200H-V can be systemmed by experts using the Certainty Factor method, with this can reduce the costs needed and also the use of time more efficiently.